Finite element tearing and interconnecting-1 method for the solution of the topology optimisation problem. (8th March 2022) - Raibi, Ouafaa; Makrizi, Abdelilah
The algebraic system derived from the descritisation of problems arising in physical field and engineering science appears to be challenging to solve due to the strong nonlinearity and the large size of such problems. Parallel processing is shown to be an efficient technique to handle the computational complexity associated with solving large linear systems and this is readily obtained by using one of the most popular methods which is known to be suitable for parallelisation, namely, domain decomposition methods. In this work, we apply finite element tearing and interconnecting method within the framework of topology optimisation, we describe a methodology that brings together existing fast algorithms for topology optimisation and FETI for solving the resulting large-scale linear systems.